PENGARUH AIR KELAPA MERAH YANG MUDA DAN TUA SEBAGAI PENGENCER TERHADAP KUALITAS SEMEN KAMBING BOER SELAMA PENYIMPANAN DINGIN - Mugiyati Mugiyati; Nurul Isnaini; Muhammad Ade Salim; Trinil Susilawati (Jurusan Produksi Ternak, Fakultas Peternakan, Universitas Brawijaya, 2017)
The aim of this research was to know the effect of maturity of red coconut water as a diluent to the sperms quality of Boer goats during chilled preservation. The research was carried out at Laboratory Sumber Sekar Faculty of Animal Husbandry University of Brawijaya Malang, on 11st December 2016 until 31st January 2017. The method used in this research was laboratory experimental using Randomized Block Design with three treatments, P0 (Tris Aminomethane + 20% Egg Yolk), P1 (Young Red Coconut Water + 20% Egg Yolk) and P2 (Mature Red Coconut Water + 20% Egg Yolk) which each treatment using 10 repetitions. The observed variables include the percentage of motility, percentage of viability and percentage of abnormal spermatozoa during chilled preservation The results showed that on the 3ndday the percentage of motility of spermatozoa during chilled preservation gave a significant effect (P<0.05), while on viability gave a very significant effect (P<0.01), and on abnormality did not give a significant effect (P> 0.05). The highest of total motile spermatozoa was P0 (Tris Aminomethan + 20% Egg Yolk). P2 better than P1 on motility, but not on viability and abnormality. The conclusions was the maturity of red coconut water can improve motility, but can not improve viability and abnormality. The suggested was use Mature Red coconut water + 20% Egg Yolk as a diluent and do further research on coconut water to be able to maintain spermatozoa longer.Keyword : Sperms, egg yolk, red coconut water, tris aminomethane